Transcription of liver X receptor is down-regulated by 15-deoxy-Δ(12,14)-prostaglandin J(2) through oxidative stress in human neutrophils. - Gonzalo Alba; María Edith Reyes; Consuelo Santa-María; Remedios Ramírez; Isabel Geniz; Juan Jiménez; José Martín-Nieto; Elízabeth Pintado; Francisco Sobrino (PLoS ONE, 2012)
Liver X receptors (LXRs) are ligand-activated transcription factors of the nuclear receptor superfamily. They play important roles in controlling cholesterol homeostasis and as regulators of inflammatory gene expression and innate immunity, by blunting the induction of classical pro-inflammatory genes. However, opposite data have also been reported on the consequences of LXR activation by oxysterols, resulting in the specific production of potent pro-inflammatory cytokines and reactive oxygen species (ROS). The effect of the inflammatory state on the expression of LXRs has not been studied in human cells, and constitutes the main aim of the present work. Our data show that when human neutrophils are triggered with synthetic ligands, the synthesis of LXRα mRNA became activated together with transcription of the LXR target genes ABCA1, ABCG1 and SREBP1c. An inflammatory mediator, 15-deoxy-Δ(12,14)-prostaglandin J(2) (15dPGJ(2)), hindered T0901317-promoted induction of LXRα mRNA expression together with transcription of its target genes in both neutrophils and human macrophages. This down-regulatory effect was dependent on the release of reactive oxygen species elicited by 15dPGJ(2), since it was enhanced by pro-oxidant treatment and reversed by antioxidants, and was also mediated by ERK1/2 activation. Present data also support that the 15dPGJ(2)-induced serine phosphorylation of the LXRα molecule is mediated by ERK1/2. These results allow to postulate that down-regulation of LXR cellular levels by pro-inflammatory stimuli might be involved in the development of different vascular diseases, such as atherosclerosis.